Modular Web Design - Curtis, Nathan (New Riders Press, 2012)
User experience design teams often suffer from a decentralized, blank canvas approach to creating and documenting a design solution for each new project. As teams repeatedly reinvent screen designs, inconsistency results, and IT teams scramble to pick up the pieces.